The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1186/scrt414
|View full text |Cite
|
Sign up to set email alerts
|

Equine mesenchymal stem cells from bone marrow, adipose tissue and umbilical cord: immunophenotypic characterization and differentiation potential

Abstract: IntroductionStudies with mesenchymal stem cells (MSCs) are increasing due to their immunomodulatory, anti-inflammatory and tissue regenerative properties. However, there is still no agreement about the best source of equine MSCs for a bank for allogeneic therapy. The aim of this study was to evaluate the cell culture and immunophenotypic characteristics and differentiation potential of equine MSCs from bone marrow (BM-MSCs), adipose tissue (AT-MSCs) and umbilical cord (UC-MSCs) under identical in vitro conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
3
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(91 citation statements)
references
References 51 publications
(144 reference statements)
11
75
3
2
Order By: Relevance
“…However, recent studies have shown that the differentiation potential of bone marrow progenitor cells and of the adipose tissue is similar (BARBERINI et al, 2014), and that the initially observed differences would due to lack of adjustments in the differentiation inducer medium necessary to the AdMSCs (STRIOGA et al, 2012). It is also worth highlighting that there are no studies comparing the therapeutic effects of MSCs from different sources (adipose tissue x bone marrow) used in equine tendinitis therapy; thus, it is necessary to conduct further investigations about it, since there are signs that the adequate source selection may broaden the effects of the cellular therapy (GARVICAN et al, 2014).…”
Section: What Is the Best Source To Be Used Adipose Tissue Or Bone Mmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent studies have shown that the differentiation potential of bone marrow progenitor cells and of the adipose tissue is similar (BARBERINI et al, 2014), and that the initially observed differences would due to lack of adjustments in the differentiation inducer medium necessary to the AdMSCs (STRIOGA et al, 2012). It is also worth highlighting that there are no studies comparing the therapeutic effects of MSCs from different sources (adipose tissue x bone marrow) used in equine tendinitis therapy; thus, it is necessary to conduct further investigations about it, since there are signs that the adequate source selection may broaden the effects of the cellular therapy (GARVICAN et al, 2014).…”
Section: What Is the Best Source To Be Used Adipose Tissue Or Bone Mmentioning
confidence: 99%
“…Since then, many isolation and featuring studies have been conducted (CARVALHO et al, 2009(CARVALHO et al, , 2013bMAMBELLI et al, 2009;BARBERINI et al, 2014). A growing number of studies assessing the impact of stem cells from adipose tissue on large animals have been conducted.…”
Section: The Mesenchymal Stem Cells From Adipose Tissue (Admscs)mentioning
confidence: 99%
“…The expression of CD markers gets changed during the subsequent cell passages in several species and also due to laboratory procedures, biological differences between the donors because of species, age, gender and site of collection [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The literature offers conflicting data regarding the risk of spontaneous transformation of mesenchymal stem cells during іn vitro culture (2)(3)(4)16). Therefore, investigations of the biological properties of mesenchymal stem cells from equine bone marrow and foal umbilical cords as well as their cytogenetic analysis are highly relevant and timely tasks (13).…”
Section: Introductionmentioning
confidence: 99%